Supply and demand analysis of organic rice the case of Don Bosco Multi-Purpose Cooperative in M'lang, North Cotabato, Philippines - Ramil, Hazel Shayne I. (School of Management, University of the Philippines Mindanao, 2016)
Organic agriculture has been growing in the Philippines specifically in Mindanao. Don Bosco Multi-purpose Cooperative located in M'lang, North Cotabato produces several healthy products mainly organic rise such as brown, black and red rice sold to its five retail outlets in Mindanao and in Quezon City. Despite increasing demand of organic rice in the market, insufficient volume due to decreasing supply of fresh "palay" became a significant problem of the cooperative. The objectives of the study include examining the factors affecting the DBMPC's demand and supply of organic rice, comparing, the productivity and profitability of organic and conventional rice farmers in M?lang, discussing perceptions towards adoption and non-adoption of organic farming and generating strategies to address problems faced by the cooperative through understanding the gap between demand and supply. These gaps were analyzed using multiple procedures on both aspects such as elasticity measures through demand modeling and descriptive statistics where data from the cooperative?s records and through conducting a survey on M'lang rice farmers are utilized. Results show that there is instability on the sales of the coop's organic rice. Also, its increasing price do not affect its demand in the market however, its price substitutes does. Regarding its supply, survey from DBMPC's organic farmers and inorganic farmers in M?lang show that those engaged in organic farming reveals 28% lower production than conventional farmers. Pests and crop disease was identified by both farmers as the most problematic in production while unsatisfactorily prices is the only problem encountered by DBMPC's farmers in the aspect of marketing. Organic farmers of DBMPC also reflects low profitability as the price offered to these farmers do not significantly differ from commercial rice. With the cooperative?s opportunity on its growing demand , improving its supply through adapting strategies such as increasing the price, adapting technologies such as Rice Duck farming and creating strong link between the government could be done to increase production and improve economic condition of DBMPC's organic farmers.